1988
DOI: 10.1042/bj2550877
|View full text |Cite
|
Sign up to set email alerts
|

The glycosylation properties of D2 dopamine receptors from striatal and limbic areas of bovine brain

Abstract: D2 dopamine receptors from bovine brain (caudate nucleus and olfactory tubercle) have been solubilized using sodium cholate/NaCl and their glycoprotein properties studied in terms of their interaction with wheat-germ agglutinin-agarose (WGA-agarose). Under optimal conditions about 65% of the applied D2 dopamine receptors bound to WGA-agarose and could be eluted with N-acetylglucosamine. The ability of receptors to adsorb to the affinity column was shown to be dependent on the cholate and salt concentrations us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Therefore these bands could represent variants at the protein level (either different gene products or proteolytic variants) or glycosylation variants. We favour the latter explanation at present as we have shown that there are at least two different glycosylation variants of the receptor based on differential binding to WGA -agarose (Leonard et al, 1988).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore these bands could represent variants at the protein level (either different gene products or proteolytic variants) or glycosylation variants. We favour the latter explanation at present as we have shown that there are at least two different glycosylation variants of the receptor based on differential binding to WGA -agarose (Leonard et al, 1988).…”
Section: Discussionmentioning
confidence: 85%
“…Even so, the images for the two receptor subtypes were both distributed around the outer perimeter of the cell body where only a limited amount of overlap in the composite confocal images could be observed. The dissimilar appearance and differential subcellular localization of D,-and D2like receptor binding fluorescence could be related to potential differences in glycosylation (Clagett-Dame and McKelvy, 1989;Jarvie et al, 1989;Leonard et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor solubilization was by a method modified from that of Leonard, Williamson & Strange (1988). Membrane pellets were stirred gently at 4°C in 10 volumes of chilled solubilization buffer (20 mM Hepes, 1 mM EDTA, 2m NaCl, 0.6%, w/v, sodium cholate and 1 mM PMSF) for 1 h and then centri¬ fuged at 100 000 g for a further 1 h. The supernatant receptor fraction was retained.…”
Section: Extraction Of Mrnamentioning
confidence: 99%